1973
DOI: 10.1159/000197419
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Levels in a Normal Veteran Population

Abstract: Pure-tone audiometric examinations of 116 non-drinking healthy veterans were compared to those of 96 subjects who consumed more than 10 ounces of pure alcohol per week. Hearing thresholds, compared by age groups, were similar in the non-drinking and drinking groups. No correlation between amount of alcohol consumed and hearing thresholds could be demonstrated in this population selected for absence of alcohol-related impairment of organ-systems other than the special senses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…78% vs. 33% ). 59 Koff et al 260 divided 431 healthy veterans participating in a larger study of normal ageing in the United States into teetotallers and drinkers who self-reported consuming more than 10 ounces of 100% alcohol per week. No differences in high frequency hearing loss were demonstrated for drinking and non-drinking groups and there was no signi® cant correlation between hearing level and amount of alcohol consumed.…”
Section: Stud Ies Of Genetic Transm Issionmentioning
confidence: 99%
“…78% vs. 33% ). 59 Koff et al 260 divided 431 healthy veterans participating in a larger study of normal ageing in the United States into teetotallers and drinkers who self-reported consuming more than 10 ounces of 100% alcohol per week. No differences in high frequency hearing loss were demonstrated for drinking and non-drinking groups and there was no signi® cant correlation between hearing level and amount of alcohol consumed.…”
Section: Stud Ies Of Genetic Transm Issionmentioning
confidence: 99%